Analysis of Intradermal Tranexamic Acid (Ta) vs Triple Combination (Hydroquinone 4%, Tretinoin 0.05%, Fluocinolone Acetonide 0.01%) Therapy for Melasma - Afsheen Bilal, Syeda Ujala Sohail, Jahangir Khan, Muhammad Rizwan Hafeez, Aftab Jameel, Abdul Hameed, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: Purpose of this study aims to compare the efficacy of intradermal tranexamic acid (Ta) therapy for the treatment of melasma with that of a fluocinolone-based triple combination therapy (Hydroquinone 4%, Tretinoin 0.05%, Fluocinolone Acetonide 0.01%). Study Design: Comparative study Place and Duration: Islamic Internatiomal Medical College Rawalpindi & Shahida Islam Medical Institute, Lodhran during the period from June ,2021 to December 2021. Methods: There were 150 cases presented, including both sexes. All of the patients who were hospitalised for treatment had melasma. After obtaining agreement in writing, a thorough demographic profile was obtained. The patients were randomly split in half. Group A was treated with a fluocinolone-based triple combination (4% Hydroquinone, 0.05% Tretinoin, and 0.01% Fluocinolone Acetonide), while group B was treated with intradermal tranexamic acid (Ta). Effectiveness was measured by contrasting the two sets of results. Results: We found that 80 (53.3%) patients were females and 70 (46.7%) patients were females. Among 150 cases, 75 (50%) had age 18-30 years, 50 (33.3%) patients had age 31-40 years and 25 (16.7%) patients had age > 40 years. Frequency of mixed melasma was higher among all cases followed by dermal and epidermal plasma. Frequency of malar-type melasma was significantly higher. We found that reduction in MASI score in group B was higher 1.9 from baseline 14.7 as compared to group A 6.1. Post-treatment we found side effects in group A and there was no any adverse outcomes observed in group B. Conclusion: In this study, we found that intradermal tranexamic acid (TA) was an effective and safe technique for treating melasma, with no clinically relevant side effects and a substantial reduction in the MASI score. Keywords: Melasma, MASI, Triple combination, Intradermal tranexamic acid